Sosialisasi Manfaat akupresure di Desa Tambah Rejo Kecamatan Gadingrejo - iga mayola pisacha (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Aisyah Pringsewu, 2023)
Acupressure is the development of an acupuncture technique that has the same purpose which is used to stimulate points in the body and press down to enter the nervous system using movement and finger pressure, namely the type of rotary press, press the point and press straight. This effort must start from instilling a healthy mindset in the community which must be initiated and cultivated by oneself. This effort is to realize the highest degree of public health as an investment for the development of productive human resources. This activity was held in Add Rejo Village, Dusun 5 and was attended by 40 people who were dominated by women. With this activity, it is hoped that there will be an increase in the understanding of acupressure and an understanding of the community to be aware of diseases that arise early so that prevention is immediately carried out. Keywords: Add Rejo Village, Acupressure, Outreach